A MULTIPRODUCT APPROACH TO PHYSICIAN OUTPUT MIX - Waples, Mary Jane (My University, 1988)
Budgetary restraints have forced a re-evaluation of expenditures for health care, regardless of the methods of delivery and financing. Efficiency in resource allocation implies production of an optimal output mix at minimum opportunity cost. Inefficiencies in resource allocation will result in higher costs. It is often argued that the fee- for-service reimbursement method, in particular, provides incentives for over-servicing, with elective surgery receiving most attention since international and intranational variations were out of line with variations in morbidity. Although the initial concern of physicians was with the clinical risks of unnecessary surgery, concern with the rising costs of providing health care has turned attention to financial factors as possible explanations of the variations in elective surgical procedures. The physician plays a key role in the allocation of resources in the health care sector. It is, therefore, likely that the aggregate output mix of different services will be responsive to the differential relative benefit rates received by physicians, with a bias in favour of the more expensive procedures and the consequent higher costs for the system as a whole. The physician's key role is emphasized in this study with the emphasis on supplier incentives and the inherent multiproduct nature of health care output. Economic theory predicts a movement along the production possibility frontier in output space in response to relative price changes. Econometric estimation of multiproduct production relations has been facilitated by the application of duality theory and the develop ment of flexible functional forms. Duality theory establishes that the parameters of the production function can be represented equally well by the corresponding dual profit or cost function. Flexible functional forms for the profit function permit derivation of supply equations with relative prices as independent variables. Four elective surgical procedures were selected in order to estimate the aggregate substitution in production by physicians. With pooled cross-section and time series data for Canada for the period 1973 to 1981, the supply equations were estimated as a system, using the SURE estimation technique. Supply elasticities for price changes and changes in the key fixed factors were calculated. While emphasis was on the price response, the functional form incorporated the constraints imposed by the availability of hospital beds and surgical specialists. Evidence was found in support of the view that physicians allocate their time partly in response to changes in the prices of elective procedures relative to other procedures. With global budget constraints imposed on hospital expenditures, the four procedures, being elective, might possibly be given lower priority. Also, the estimated coefficients for the lagged dependent variables suggest that an inertia model of adjustment applies. Although incentives may exist in the fee structure to substitute toward the more expensive procedures, the results suggest that, at least for the period of the study, substitution was not on the basis of price alone, and that resource constraints, as proxied jointly by the number of hospital beds and surgical specialists, play a greater role in determining aggregate output.
Keywords: Health Care; Expenditure; Finance; Fee-for-service; Economic theory; Surgery